곰팡이 코곁굴염에서 발생한 뒤허혈시신경병증 의증 1예 - 양승안; 김수진 (Daihan angwa haghoi jabji, 2023)
목적: 곰팡이 코곁굴염에서 발생한 뒤허혈시신경병증 1예를 보고하고자 한다. 증례요약: 81세 남자 환자가 3주 전 발생한 갑작스런 좌안의 시력저하로 내원하였다. 최대교정시력은 우안 0.6, 좌안 광각인지로 측정되었고, 양안 동공 모두 3 mm로 동공부등은 없었으며, 좌안의 상대구심동공운동장애가 관찰되었다. 안저검사에서 양안의 당뇨망막병증이 관찰되었으나 양안 시신경유두함몰비 증가 외에 시신경유두의 부종이나 출혈 등 특이 소견 보이지 않았고, 형광안저촬영에서도시신경유두의 충만지연이나 결손, 형광누출은 관찰되지 않았다. 좌안 시신경병증의 원인 감별을 위해 시행한 뇌 자기공명영상에서양쪽 코곁굴염이 나비굴, 벌집굴, 이마굴에 걸쳐 광범위하게 관찰되었다. 이비인후과에서 시행한 수술 중 안와 첨부 및 시신경관과코곁굴의 경계부는 침범되지 않았으나, 조직검사상 aspergillosis로 확인되어, 곰팡이 코곁굴염과 동반한 뒤허혈시신경병증으로 추정진단하였다. 결론: 당뇨 조절이 되지 않는 고령의 환자에서 통증 없이 갑작스런 시력저하가 발생하는 경우 곰팡이 코곁굴염과 동반한 뒤허혈시신경병증을 감별진단에 두고, 즉각적인 영상검사와 적절한 치료를 해야 한다. Purpose: We report a case of probable posterior ischemic optic neuropathy in a patient with acute fungal sinusitis. Case Summary: An 81-year-old male patient presented with sudden-onset visual loss in his left eye 3 weeks prior to presentation. His best corrected visual acuity was 0.6 in his right eye and light perception in his left eye. Pupillary size was 3 mm in both eyes, and a relative afferent pupillary defect was detected in his left eye. In fundus examination, diabetic retinopathy was found, and cup/disc ratios were increased in both eyes, but disc swelling and hemorrhage were not observed. Fluorescein angiography did not indicate filling delay, defects, or leakage of discs in either eye. Magnetic resonance imaging of the brain revealed multi-sinusitis in the sphenoid, ethmoid, and frontal sinuses. No bony defects or erosion were found around the optic canal or orbital apex during endoscopic surgery; however, histological examination revealed aspergillosis. The patient was diagnosed with posterior ischemic optic neuropathy caused by acute fungal sinusitis. Conclusions: When elderly patients with uncontrolled diabetes experience sudden visual disturbances without ocular pain, posterior ischemic optic neuropathy with fungal sinusitis should be considered as a differential diagnosis. Immediate imaging studies and appropriate treatment should be performed. KCI Citation Count: 0